محاولات الانتحار بين أزمة الوجود وأزمة الاتصال: مقاربة سوسيو - ثقافية - كبداني، خديجة (جامعة وهران2 محمد بن أحمد, 2018)
Suicide or more explicitly suicide attempts in our society have taken another dimension. People in such a situation do no longer aim at killing themselves but put an end to a dramatic situation, which pushes the individual towards distress and hopelessness. This insuperable situation of clash between mutations and factors is due to the family or social system the individual belongs to. In the light of these mutations, the instrumental communication has taken a material dimension where the individuals have lost all interaction and emotional sharing. This loss of affective and interactive communication has established suicide attempts as an escape link between the family and society, and these acts, therefore, show the absence of communication. The main objective of this paper/study/intervention is to target a group of young people as a sample in order to inquire into the problems causing harm to this category of young people amongst their family and their society and what solutions they consider to overcome these problems; and then work with suicidal people and define the factors pushing them to this act.
Keywords: علم النفس الاجتماعي -- الاضطرابات النفسية -- التواصل الاجتماعي